Cloud-Based Inventory Control Improves Order Fulfillment Accuracy For University Micro-Entrepreneurs - Ahmad Nizar Yogatama; Fadilla Cahyaningtyas; Rita Indah Mustikowati; Zurina Binti Zulkifli; Widiya Dewi Anjaningrum (Jurnal Pengabdian Masyarakat, 2026)
Purpose: This study addresses inventory mismanagement among Shopee student-preneurs, specifically tackling dead-stock accumulation, stockouts, and limited storage that trigger order cancellations and penalize store performance. Method: A six-month intervention engaged twenty fashion student-preneurs at ITB Asia Malang through structured phases. The program implemented a cloud-based Google Sheets system with Reorder Point formulas, utilizing pre/mid/post-tests and operational tracking. Practical Applications: The digital tool enables real-time stock monitoring, automated alerts, and data-driven procurement. This cost-effective model helps e-commerce micro-entrepreneurs optimize limited storage, prevent capital lock-up, and streamline fulfillment workflows. Conclusion: Cognitive mastery improved significantly from 40 to 85. The system substantially reduced stockouts and dead stock, enhancing operational efficiency. Despite external supplier variables, cloud-based inventory control successfully improves order fulfillment accuracy and business sustainability.